Communication skills with children in paediatric anaesthesia: challenges while wearing a face mask. Issue 1 (27th October 2020) - Crowe, Ann-Marie Lydia
Abstract : Effective communication with children is a skill, the importance of which is especially highlighted by the COVID-19 pandemic and the ubiquitous wearing of face masks. Anaesthesiology consultants have been shown to display excellent communication skills that facilitate the development of rapid rapport and patient cooperation. Good communication results in positive interactions for hospitalised children, which correlates with improved healthcare outcomes. However, interactions with a child aren't always straightforward, particularly for trainees unfamiliar with certain communication techniques, which are important to use at a time when when the wearing of face masks is commonplace.